Sisters in Science Conversations with Black Women Scientists on Race, Gender, and Their Passion for Science - Jordan, Diann (Purdue University Press, 2006)
Author Diann Jordan took a journey to find out what inspired and daunted black women in their desire to become scientists in America. Letting 18 prominent black women scientists talk for themselves, Sisters in Science becomes an oral history stretching across decades and disciplines and desires. From Yvonne Clark, the first black woman to be awarded a B.S. in mechanical engineering to Georgia Dunston, a microbiologist who is researching the genetic code for her race, to Shirley Jackson, whose aspiration led to the presidency of Rensselaer Polytechnic Institute, Jordan has created a significant record of women who persevered to become firsts in many of their fields. It all began for Jordan when she was asked to give a presentation on black women scientists. She found little information and little help. After almost nine years of work, the stories of black women scientists can finally be told.